Ground beetle (Coleoptera: Carabidae) community structure at the early stage of forest regeneration after sanitary logging of oxalidosum spruce forest in Belovezhskaya Pushcha - Kazulka, Mikalai G.; Kazulka, Heorhi A. (Experimental Biology and Biotechnology, 2017)
Data on the effect from sanitation harvest upon community structure of ground beetles in the Oxalidosum spruce forest in Belovezhskaya Pushcha are given. 3028 specimens of ground beetles belonging to 45 species were collected by using pitfall traps and 42 specimens of 12 species were collected by quadrate method from April to November 1992. The structure of ground beetle communities in the forest area and the adjacent logging plot were examined. Calathus micropterus, Carabus arcensis, Carabus hortensis, Carabus nemoralis, Pterostichus niger, Pterostichus oblongopunctatus and Trechus secalis prevailed. Increasing in species diversity and reducing in the number of ground beetles after deforestation was established. Decreasing in the number of most forest species and increasing in the number of species of open habitats and the forest species Trechus secalis was recorded on the logging plot. Data obtained by pitfall traps were largely confirmed by quadrate method.
Keywords: carabid beetles; species composition; spruce forest; logging; Belovezhskaya Pushcha